1999
DOI: 10.1021/jp9903099
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate Geometry Distinction in Arenethiols by Ion/Surface Reactive Collisions

Abstract: Reactive scattering of low-energy ions from surfaces gives scattered product ions in which new bonds are formed with the adsorbate with a sensitivity to adsorbate geometry. Reactions of Cr •+ and C 5 H 5 N •+ , as well as chemical sputtering induced by Xe •+ , are used to distinguished two well-characterized monolayer systems, namely 1,4-benzenedimethanethiol (BDMT) adsorbed on Au(111) and Ag(111) thin films. While the reaction of Cr •+ with the Au monolayer produces an ion assigned as CrC 7 H 5 S + , this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Different reaction products formed by collisions of Cr ϩ• and C 5 H 5 N ϩ , as well as chemical sputtering induced by Xe ϩ. helped to elucidate the 1,2-and 1,4-BDMT geometry on both Au and Ag surfaces. 202 Finally, as discussed previously, abstraction reactions from surfaces are typically indicative of the nature of the surface. These abstraction reactions, whether of hydrocarbon 91,202 or fluorocarbon groups, 180 provide detailed information about the surface.…”
Section: Surface Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…Different reaction products formed by collisions of Cr ϩ• and C 5 H 5 N ϩ , as well as chemical sputtering induced by Xe ϩ. helped to elucidate the 1,2-and 1,4-BDMT geometry on both Au and Ag surfaces. 202 Finally, as discussed previously, abstraction reactions from surfaces are typically indicative of the nature of the surface. These abstraction reactions, whether of hydrocarbon 91,202 or fluorocarbon groups, 180 provide detailed information about the surface.…”
Section: Surface Analysismentioning
confidence: 93%
“…Similar conclusions were reached when low energy reactive ion/ surface collisions were used to investigate the adsorption geometry of 1,2-1,3-, and 1,4-benzenedimethanethiol SAM surfaces. 202 Characteristic differences in the scattered ion products collected from each SAM were used to elucidate the adsorption geometries.…”
Section: G Analysis Of Modified Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilayers and multilayers have been built by the oxidative formation of a S-S bond between dithiols, although these reactions depend on the presence of oxidants in the solution [10][11][12][13][14][15][16]. The addition of a reductor as tri-n-butylphosphine prevents the formation of multilayers and allows the generation of well-ordered monolayers of the dithiol in which the molecules adopt a standing-up orientation [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, adsorbed chlorobenzyl mercaptan isomers [5] can be differentiated based on reactions with Cr •+ , which generate such product ions as CrCl + and CrC 7 H 6 Cl + with the accessible chlorine in the p-chloro isomer. In another study [26], the molecular ion of pyridine, C 5 H 5 N •+ , was shown to allow distinction between 1,4-benzenedimethanethiol adsorbed on gold versus silver due to differences in the orientation of the adsorbates on the two metals.…”
Section: Introductionmentioning
confidence: 99%